1973
DOI: 10.1007/bf01870006
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial permeability for alcohols, aldoses, and amino acids

Abstract: Summary. Mitochondria isolated from potato tubers were placed in solutions containing various alcohols, aldoses, or neutral amino acids. Based on the osmotic responses in the different media, the reflection coefficients and hence the relative permeabilities of the nonelectrolytes could be determined. The reflection coefficients (afs) of the potato tuber mitochondria for alcohols became progressively larger as hydroxymethyl groups were added to the molecule, viz. If we increase the osmotic pressure in a solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1974
1974
1982
1982

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Finally, two studies deal with alcohol effects on permeability proper. In one, permeation of alcohols into mitochondria was found to decrease as the number of OH groups increases ( 17). In the other, with an artificially thin lipid membrane from sheep red cells, Gutknecht and Tosteson (4) reported that aliphatic alcohols lower the resistance of this membrane to ions and especially that they increase its permeability to K+.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, two studies deal with alcohol effects on permeability proper. In one, permeation of alcohols into mitochondria was found to decrease as the number of OH groups increases ( 17). In the other, with an artificially thin lipid membrane from sheep red cells, Gutknecht and Tosteson (4) reported that aliphatic alcohols lower the resistance of this membrane to ions and especially that they increase its permeability to K+.…”
Section: Discussionmentioning
confidence: 99%